(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: Drowning is a form of asphyxia due to the aspiration of fluid into air-passages, caused by submersion in water or other fluid. The death mechanism of drowning is very complicated with the involvement of asphyxia and filling of air-passage with the fluid along with effects at a hydrostatic and osmotic level. Material and methods: In this study, all autopsied cases of fresh drowning-dead body having no decomposition signs at the Tertiary Care Hospital, Bhavnagar, Gujarat, are included, during the period of 1-year 1stSept. 2019 to 31stAug. 2020. From total of 914 autopsy, 25 cases were of fresh drowning. Results & Conclusion: The majority of the cases with drowning were males (88%). Froth was one of the most characteristic external signs of drowning- found in (68%) of cases. On internal examination lungs are heavy and voluminous in (56%).